Carbon-lite collaboration: a virtual visual matrix. (1st July 2020) - Hollway, Wendy; Kofoed, Jette; Ruch, Gillian; Sims, Louise; Thomson, Rachel; Tonkin, Lois
Abstract : In this article we present an example of psychosocial practice ‐ a visual matrix ‐ which attempted to address and embody carbon-lite research methods in the face of global heating. Combining virtual and face-to-face modes of presence and interaction generated insights as well as posing challenges. In the article we explore two ideas through a discussion of 'interference' and 'inclusion/exclusion'. The article extends our understanding of the method to include an awareness of what comes before and after the matrix. By attuning ourselves to its materialities and the practices of care involved in staging a matrix and then digesting its affects and effects, we are alerted to the front and back stage of the method. Following this insight we discuss how a feminist engagement with psychosocial method can be used to connect 'matters of concern' such as global heating with situated practices of care that themselves may constitute a carbon-lite methodology. The article is polyvocal, generated by participants through virtual communication in the month following the matrix. It documents an intense, rich and finite period of communication and collaboration. It is an example of 'writing which offers to us a space where we are able to confront reality in such a way that we live more fully' (Back, 2007: 160). Questions of mortality and finitude are a motif for the matrix, expressed in a range of ways.